2004
DOI: 10.1111/j.1365-2249.2004.02585.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ-modified dendritic cells suppress B cell function and ameliorate the development of experimental autoimmune myasthenia gravis

Abstract: SUMMARYThis study was designed to investigate the therapeutic effects of interferon (IFN)-g -modulated dendritic cells (DC) in experimental autoimmune myasthenia gravis (EAMG). We induced EAMG in Lewis rats by immunization with Torpedo nicotinic acetylcholine receptor (nAChR) and adjuvant. On day 33 postimmunization (p.i.), splenic DC were prepared, exposed to IFN-g alone (IFN-g -DC) or to IFN-g in combination with 1-methyl-DL-tryptophan (1-MT), the specific inhibitor of indoleamine 2,3-dioxygenase (IDO) (IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…In another experiment, pretreatment of splenic DCs from naive mice with IFN-␥ in vitro directly suppressed the Ag-presenting capacity of DCs (Fig. 6J), which was consistent with previous studies (42)(43)(44). Moreover, pretreatment of DCs with IFN-␥ attenuated eosinophilic inflammation induced by transfer of OVA-pulsed DCs and inhalation of OVA (Fig.…”
Section: In Vivo Ifn-␥ Gene Delivery Suppresses Overall DC Functions supporting
confidence: 89%
“…In another experiment, pretreatment of splenic DCs from naive mice with IFN-␥ in vitro directly suppressed the Ag-presenting capacity of DCs (Fig. 6J), which was consistent with previous studies (42)(43)(44). Moreover, pretreatment of DCs with IFN-␥ attenuated eosinophilic inflammation induced by transfer of OVA-pulsed DCs and inhalation of OVA (Fig.…”
Section: In Vivo Ifn-␥ Gene Delivery Suppresses Overall DC Functions supporting
confidence: 89%
“…The significance of this discrepancy becomes obvious when considering that MSCs pretreated by IFN-g became powerful inhibitors of activated B-cell growth. Interestingly, dendritic cells exposed to IFN-g before injection acquire therapeutic potential in an experimental autoimmune myasthenia gravis rat model, in association with an IDO-dependent inhibition of B-cell function in vivo (35).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that in rats, presentation of AChR epitopes by unsuitable APCs (fixed B cells that had been incubated with AChR under conditions favoring AChR uptake and processing) caused unresponsiveness of the AChR-specific CD4 + T cells to further stimulation with AChR (113). More recently, several studies have demonstrated that DCs, especially after treatment with TGF-β, IFN-γ, or IL-10, when injected into rats with developing or ongoing EAMG, suppressed or ameliorated the myasthenic symptoms (114)(115)(116). The effect was correlated with a reduced production of anti-AChR Abs without a reduced proliferative response of T cells to the AChR.…”
Section: The Futurementioning
confidence: 99%